PERAN ORANG TUA MERUPAKAN FAKTOR DOMINAN TERHADAP PERILAKU SEKSUAL REMAJA - Erna Mesra Mesra; Fauziah Fauziah (Jurnal Ilmu dan Teknologi Kesehatan, 2015)
Sexual behavior is anindividual actions to express her or hisselves attitude sexually, including howto speak and how to act. Data from BKKN shows that during the year 2010, the number of singlewomen who had lost her virginity in Medan, Bandung, Yogyakarta were respectively 52%, 47%, and37%. In relation to HIV/AIDS, 21.1770 people are AIDS positives and 47.157 people are HIV positive.They consist of people aged 20-29 years (48,1%), and aged 30-39 years (30,9%). Goals :to identifythe incidence of sexual behaviors in adolescents and determinant factors associated with sexualbehavior. Desain study is cross sectional with 155 people as sample. Result: there are 51,8% ofrespondents express severe sexual behaviour, and 6,45% experienced sexual intercourse.There isrelationship between gender, reproductive health knowledge, attitudes, parental education,neighbourhood, peers, parents' role and sexual behaviour. The most dominant variable is the role ofparents with OR 27 343. It means that parents figure made a chance to more or less severe sexualbehavior about 27.343. Suggestions: Initiatives and program development to improve adolescentsreproductive health knowledge and to provide counseling sexual behavior and required. Parentsshould keep close to their teenagers,be a friend, be available when they need support and advice.